Gastric polypoid intramucosal carcinoma and an adjacently located leiomyoma at the cardia - Arzu ÇELEBİ KOBAK and Müjdat ZEYBEL and Semin AYHAN and Ahmet AYDIN and Yavuz KAYA and Ender ELLİDOKUZ (Turkish Journal of Gastroenterology, 2019)
-